Factors associated with lower social activity in german older adults at increased risk of dementia: a cross-sectional analysis - Buchholz, Maresa; Zöllinger, Isabel; Thyrian, Jochen René; Luppa, Melanie; Zülke, Andrea; Döhring, Juliane; Lunden, Laura; Sanftenberg, Linda; Brettschneider, Christian; Czock, David; Frese, Thomas; Gensichen, Jochen; et al. (Journal of Alzheimer's disease, 2024)
Background: Studies demonstrate associations between low social activity in older adults and cognitive decline. Little has been investigated regarding which factors are associated with low social activity in older adults at increased risk of dementia. - Objective: We investigate which sociodemographic, psychological, health-related, and environmental factors are associated with low social activity in older adults at increased risk of dementia. Additionally, we describe the stages of health behavior change, the types of social activities, and the duration of the current level of social activity. - Methods: We used baseline data of 1,015 participants from the AgeWell.de trial. We conducted logistic and Poisson regression analyses to investigate factors associated with low social activity. We report descriptive statistics on the stages of change in the sample, the types of social activities most frequently pursued, and the duration of the current level of social activity. - Results: Lower income, non-usage of public transport, depressive symptoms, cognitive, mobility, and hearing impairment were negatively associated with social activity. The majority of the sample was in the maintenance stage, followed by the precontemplation stage. The most common social activities were traveling and hobbies with others. Participants have maintained their current level of social activity for several years. - Conclusions: We identified a lack of resources (income, transport), depressive symptoms and poorer health (cognitive, mobility and hearing impairment) as barriers to social activity. Interventions promoting social activity in older adults at risk of dementia may specifically target individuals with these risk factors. Low-threshold opportunities for social activity may be particularly beneficial.
Gesehen am 22.12.2025
Online veröffentlicht am 6. April 2024